(untitled) (Docentes 2.0 Journal, 2023)
The evolution of research in neuroscience and cognitive processes has revolutionized our way of seeing the brain and its functions. The purpose of this investigation was to examine the national and international state-of-the-art sources related to how lateral development methodologies, as well as the CoRT program, influence the lateral development of students. A systematic review of the literature on descriptive typology was carried out. An exploratory documentary narrative design with a quantitative approach was chosen, following the guidelines and recommendations established in the PRISMA declaration. Seventeen works were identified by applying the established inclusion and exclusion criteria. The systematic review made it possible to highlight a crucial importance in the current education landscape. The focus of the new lateral development methodologies, together with the influence of the CoRT program, highlighted the ability to cultivate lateral and creative thinking in students, impacting their learning process and laying the foundations for long-term personal and professional development.